Impact of propagation model on capacity in small-cell networks - Sousa, Sofia (2017)
This work evaluates the impact of different path loss models on capacity of small cell (SC) networks, including the relationship between cell size and capacity. We compare four urban path loss models: the urban/vehicular and pedestrian test environment from the ITU-R M. 1255 Report, and the two-slope Micro Urban Line-of-Sight (LoS) and Non-Line-of-Sight (NLoS) models from the ITU-R 2135 Report. We show that when using the ITU-R two-slope model that considers the existence of a break-point in the behaviour of path loss, for coverage distances, R, up to break-point distance divided by reuse factor, supported cell throughput, Rb-sup, is much lower than expected when traditional single-slope models are assumed. For Rs longer than dBP/rcc the results for Rb-sup increase with R, whereas they are steady or decrease with R when using the traditional single-slope propagation models. We conclude that the two-slope propagation model yields a significantly lower throughput per square km than a traditional one-slope model if and only if cell radius is small.